PEMANFAATAN APLIKASI PEMBUKUAN ONLINE UNTUK USAHA MIKRO KECIL MENENGAH UMKM DI DESA KARANGANYAR KABUPATEN KARAWANG - Septiana Rahayu; Mega Rianita Kartika; Bayu Priyatna (Jurnal Abdi Citra, 2026)
An Android-based application can serve as a solution for Micro, Small, and Medium Enterprises (MSMEs) in Karawang Regency in preparing financial statements. The application can assist business owners in recording financial transactions easily and updating them using a smartphone, enabling them to monitor in real time whether their businesses are financially healthy or not. However, it is essential to provide education and training for MSME owners regarding the benefits of financial reporting and the proper use of the application. In addition, efforts should be made to increase MSME owners' awareness and understanding of the importance of accounting in business management through targeted campaigns and outreach programs. These initiatives can help improve the quality of financial management practices among MSMEs in Karawang Regency.